Uji Validitas dan Reliabilitas Konstruk Resiliensi Ego Menggunakan SEM - Rahmah Fitroh; Hadi Suyono (Fakultas Psikologi, Universitas Putra Indonesia YPTK Padang, 2020)
The purpose of this study was to examine the validity and reliability of the ego resilience construct using SEM. The subjects of this stuudy were vocational high school students in Martapura who tested 149 students. The research scale uses ego resilience scale made by researchers developing from Shin and Park (2013). The scale is arranged based on a scale based on its aspects consisting of 24 statements with 4 alternative answer choices. The scale was analyzed using Sem AMOS software version 24. The result showed that 10 statements were valid and reliable